Perspectives on Leadership in Different Conditions of Local Enterprises (Economic journal of Lesya Ukrainka Volyn National University, 2018)
Developing scientific and practical approaches to local companies management will improve its critical financial indicators and guarantee financial support of local governments. Companies employees’ can have excellent leadership skills, but in some circumstances, they can’t use it correctly.  In such a case a company should intensify a process of its proper usage. On the results of the employee potential analysis, the paper improved the methodology of situational leadership influence. The authors established that when companies have threatened position and risk situation, they are, in particular in high demand of their leaders. The paper allocated a new management process – management of leadership. It provides the development of new leadership approaches. There are some areas which improve such a theory. First, it takes into account characteristics of the local enterprises and its social mission, in particular. Also, it includes investing intensification as well as the social responsibility of the company. Second, It expands management field, such as employee relations management, total quality management, crisis management, etc. Finally, it informs about possible threats in the area of leadership, including unsuccessful recruitment, failure of leadership implementing, and leads to increase management efficiency.
Keywords: intensification of leadership potential, situational leadership theories, crisis activity conditions, educational-professional potential, career potential, motivational potential, communicative potential.